Book Review: Accounting, Capitalism and the Revealed Religions - Firmansyah, Irman (Review on Islamic Accounting, 2025)
This article discusses the relationship between accounting, capitalism, and the three revealed religions—Judaism, Christianity, and Islam—as analyzed by Vassili Joannidès de Lautour. Through an interdisciplinary approach encompassing the philosophy of religion, sociology, and economic history, this book explains how accounting practices are rooted not only in economic needs but also in the theological and moral dimensions of these major religions. Accounting is seen as a means of human accountability to God and fellow humans, while capitalism is considered a worldly manifestation of specific religious values. This book affirms that accounting is a moral reflection of humanity about God and itself. It does not only count numbers, but also weighs meaning; it does not only record transactions, but also writes the ethical history of civilization. Therefore, the sustainability of the world economy will greatly depend on the extent to which accounting can once again become a tool of balance between material profit and spiritual responsibility.